Comparative kinetic analysis of redox flow battery electrolytes: From micro-fibers to macro-felts. (20th July 2022) - Feynerol, Vincent; El Hage, Ranine; Brites Helú, Mariela; Fierro, Vanessa; Celzard, Alain; Liu, Liang; Etienne, Mathieu
Abstract: In the context of new aqueous organic electrolytes development for redox flow batteries, two different approaches of charge transfer kinetic constant determination on carbon-based felts are compared. The first one consists in direct electrochemical measurement on centimetric pieces of felts, referred to as macro-felts, and the second is based on electrochemical measurement on carbon fibers extracted from felts and conditioned as microelectrodes, referred to as micro-fibers. Quantitative cyclic voltammetry (CV) involving experimental data fitting or simulation and electrochemical impedance spectroscopy (EIS) are carried out on the two supports, with two typical aqueous organic electrolytes, and determined values for charge transfer kinetic constants are compared. k 0 values analyzed from micro-fibers are systematically lower than that analyzed from macro-felts where the differences may reach ca . two orders of magnitude in some cases. CV and EIS analysis on micro-fibers show very good consistency. With the simplicity of physical analysis, micro-fibers are considered as a reliable and powerful tool for kinetic determination, especially when confronted to fast kinetics.